2009
DOI: 10.1007/s11418-009-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation and bioactivation of isoflavones from Pueraria flowers by human intestinal bacterial strains

Abstract: The flowers from Pueraria, which are called Puerariae Flos, have been used since ancient times for recovery from alcohol intoxication. We elucidated the microbial transformation of the main isoflavones (1, 1a and 2) by using 29 commercially available human intestinal bacterial strains together with the bioactivation of the hepatoprotective activity of their metabolites. Tectoridin (1a), which contains only one glucosyl moiety, was metabolized to its aglycone 1b by various bacterial strains. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
(21 reference statements)
1
29
0
Order By: Relevance
“…Comparison of amounts of saponins and isoflavones in extracts of Pueraria flowers Table 2 indicates the amounts of saponins (1-3) and isoflavones (4)(5)(6)(7)(8)(9)(10)(11)(12) in each specimen. The amounts of total isoflavones in each year obtained from the collected flowers of P. lobata (#1-7) were almost consistent (1.84-2.86%).…”
Section: Comparison Of Hplc Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of amounts of saponins and isoflavones in extracts of Pueraria flowers Table 2 indicates the amounts of saponins (1-3) and isoflavones (4)(5)(6)(7)(8)(9)(10)(11)(12) in each specimen. The amounts of total isoflavones in each year obtained from the collected flowers of P. lobata (#1-7) were almost consistent (1.84-2.86%).…”
Section: Comparison Of Hplc Profilesmentioning
confidence: 99%
“…Some biological activities of Puerariae Flos and its constituents have already been elucidated, and include detoxification of alcohol [1][2][3][4][5][6], hepatoprotection [2,3,7,8], anticomplementary activity [9], and estrogenic activity [10]. Very recently, we reported microbial transformation of isoflavones and bioactivation by intestinal bacteria [11]. Both types of Puerariae Flos contain a large amount of isoflavones and saponins (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the hydrolysis of the sugar moiety is required for isoflavone bioavailability and that isoflavone glycosides are not absorbed intact across the enterocyte in healthy adults [6]. When cultured with enteric bacteria, tectoridin and TGXG are metabolized into tectorigenin and 6HGDG is metabolized into the aglycone isoflavone 6-hydroxygenistein [7,8]. Consequently, the major isoflavones in PFE are likely to be absorbed into the bloodstream in the forms of tectorigenin and 6-hydroxygenistein.…”
Section: Introductionmentioning
confidence: 99%
“…Bioconversion is an eco-friendly and efficient method for enhancing the bioavailability of glycosylated stilbenes. Bioconversion of prodrugs enhances bioavailability [15], and bioconversion processes have been applied in various fields to improve the biological activity of bioactive molecules [2,20,25,30]. Enzymatic conversion of glycosides into aglycones enhances their biological activities [18,21,22].…”
Section: Introductionmentioning
confidence: 99%